The Culture of Mental Illness and Psychiatric Practice in Africa - Kleinman, Arthur; Hill, Allan G.; Akyeampong, Emmanuel Kwaku (Book collections on Project MUSE., 2015)
In many African countries, mental health issues, including the burden of serious mental illness and trauma, have not been adequately addressed. These essays shed light on the treatment of common and chronic mental disorders, including mental illness and treatment in the current climate of economic and political instability, access to health care, access to medicines, and the impact of HIV-AIDS and other chronic illness on mental health. While problems are rampant and carry real and devastating consequences, this volume promotes an understanding of the African mental health landscape in service.